Advancements in Laparoscopic Techniques for Perineal Hernias—Technical Success and Complications Data - Sarah Kalmbach; Hannah Laura Welskopf; Christoph Steidle; Philipp Horvath; Robert Bachmann (Gastrointestinal Disorders)
Purpose: Multimodal approaches, including radiochemotherapy and surgical resection, are commonly used to treat rectal malignancies. Postoperative perineal hernias, though not uncommon, have shown an increasing incidence in recent years. Managing symptomatic perineal hernias presents a challenge, with a high recurrence rate after repair. This retrospective study investigates the laparoscopic placement of a non-absorbable mesh for treating pelvic floor hernias involving bowel displacement. Methods: This study included all consecutive patients requiring hernia repair due to symptomatic perineal hernias following minimally invasive abdominoperineal resection. All patients had a history of local radiation therapy. Data were collected on surgery duration, intra- and postoperative complications, and hernia recurrence rates. Results: Laparoscopic displacement of the small bowel from the pelvis was performed on eight patients, and closure of the pelvic floor hernia area was achieved using non-absorbable mesh placement. All procedures were successful, and no perioperative complications were recorded. Only one early complication occurred, classified as Clavien-Dindo II. Conclusions: The laparoscopic procedure, serving as a safe method for repositioning the small intestine and closing a perineal hernia using a mesh, has shown promising outcomes. The use of a non-absorbable mesh as an alternative to native tissue appears to be effective, with no observed recurrent hernias. However, further evaluation through long-term results or a larger cohort study is still pending.